A agricultura familiar e a permanência da população no campo no município de Quitandinha região metropolitana de Curitiba - Siqueira, Juliana Margarida (2016)
The State of Paraná has passed through deep turns, such as the modernization of agriculture accentuated after 70's, when the most of the population gave up of the countryside and move on to the cities. We observe in the Metropolitan Region of Curitiba (MRC) that process from two angles: first, the "reception" of the migrant (where many of those people were directed to rural areas) and second, the "expulsion" of the population that migrates from rural to urban zones. The intense industrialization by which the state's capital attracted population from the countryside both to Curitiba and in the nearest cities. Despite of the industrial development and the MRC services sector growing, the migrant population retains some peculiarities: the low urbanization degree in several cities and its remarkable dependence on Familiar Agriculture. Before this reality, the goal of this study is to analyze city of Quitandinha that has the majority of the population living in the countryside. From specific theoretical frameworks and local visitations, we observed that this city has a rich and diverse Familiar Agriculture, especially for the production of vegetables and tobacco. According to the collected data, the most people like to live there, including young people. Thus, it can be considered that the permanence of Quitandinha rural population is related to the cultural aspects, since most people are descendants of European immigrants and have strong ties to the land. Those familiar farmers have a relatively medium to high socioeconomic level because keep market relations with the regional market. However, to start at the marketing those families stay subjected to the action of capital, frequently the main alternative to stay on their land since they don't hold collective organizations to change this situation.